Tweeting Over Time: Twitter/X for Communication, Assessment, and Growth in Middle Level Teacher Education - Toni M. Williams (Current Issues in Middle Level Education)
This article shares how preservice Middle Level teacher candidates used social media, specifically Twitter/X as both a resource and a tool and how that tool became important in assessing student growth and knowledge building which, in turn, informed instructional planning for the teacher education classroom. This is paramount for teacher educators and the future educators they teach, as they are preparing to create a variety of engagements for learning in teacher education programs and in middle level classrooms. Creating an online community is a means in which all preservice teachers can use their voices while at the same time having their voices heard also providing a model for them to use as they move into their own classrooms.